Targeting H3K27me3 demethylase to inhibit Shh signaling and cholesterol metabolism in medulloblastoma growth - Deng, Hongshi; Guo, Xueli; Feng, Na; Luo, Yi; Liu, Bei; Liu, Shuzhen; Wu, Jiang I.; Shi, Xuanming (Frontiers in Oncology, 2022)
Previously we uncovered the epigenetic regulation of medulloblastoma that low levels of H3K27me3 are required for Shh target gene expression and medulloblastoma growth. Since Jmjd3, an H3K27me3 demethylase, is responsible for maintaining low H3K27me3 at Shh target genes, targeting Jmjd3 could be an efficient way to inhibit Shh signaling and medulloblastoma growth. Here we show that the small molecule GSK-J4, an inhibitor of Jmjd3, significantly inhibited the expression of Shh target genes in Shh responsive cell models and primary cerebellar granule neuron precursors. GSK-J4 also significantly reduced the growth of primary Shh medulloblastoma cultures. Treating human medulloblastoma cell line DaoY by GSK-J4 led to cell cycle arrest at G0/G1 phase with decreased cells in S-phase. Tumor cell proliferation was significantly inhibited by GSK-J4 treatment. Gene expression analyses showed that GSK-J4 additionally constrained the expression of key genes in cholesterol biosynthesis. Our results highlight the possibility that targeting H3K27me3 demethylase Jmjd3 with GSK-J4 to inhibit Shh signaling and cholesterol metabolism is a potential application to treat Shh medulloblastoma.